2020
DOI: 10.1111/cas.14440
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantification of urinary metabolites for predictive models manifest clinicopathology of renal cell carcinoma

Abstract: Using surgically resected tissue, we identified characteristic metabolites related to the diagnosis and malignant status of clear cell renal cell carcinoma (ccRCC). Specifically, we quantified these metabolites in urine samples to evaluate their potential as clinically useful noninvasive biomarkers of ccRCC. Between January 2016 and August 2018, we collected urine samples from 87 patients who had pathologically diagnosed ccRCC and from 60 controls who were patients with benign urological conditions. Metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Similarly, elevated urinary levels of 3-oxyAA were found in patients with renal cell carcinoma (RCC), though changes in 3-oxyKYN were statistically insignificant [101]. Contrary to previous studies, Sato et al postulated that elevated urinary KYN concentration is a predictive marker of RCC malignancy [102]. In another study, elevated serum KYN and 3-OHAA concentrations were found in a group of 24 patients treated with IFN-γ for metastatic carcinoma, with a concomitant decrease in KYNA levels [103].…”
Section: Kidney Cancermentioning
confidence: 99%
“…Similarly, elevated urinary levels of 3-oxyAA were found in patients with renal cell carcinoma (RCC), though changes in 3-oxyKYN were statistically insignificant [101]. Contrary to previous studies, Sato et al postulated that elevated urinary KYN concentration is a predictive marker of RCC malignancy [102]. In another study, elevated serum KYN and 3-OHAA concentrations were found in a group of 24 patients treated with IFN-γ for metastatic carcinoma, with a concomitant decrease in KYNA levels [103].…”
Section: Kidney Cancermentioning
confidence: 99%
“…Multivariate analysis was undertaken using multiple logistic regression analysis. 17 Receiver operating characteristic curve analysis was used to evaluate the diagnostic performance of the resulting regression model based on its AUC, sensitivity, and specificity values. Survival curves were plotted using the Kaplan-Meier method and statistical significance was assessed using the log-rank test.…”
Section: Discussionmentioning
confidence: 99%
“…24 Metabolism of cancer patients has been reported to be distinct from that of patients without cancer. 17 We previously reported that and inositol pathways increased in patients with cancer compared to those without. 17 By comparing these differences, metabolomics has been evaluated in several diseases to identify new biomarkers.…”
Section: F I G U R Ementioning
confidence: 94%
See 2 more Smart Citations